2015
DOI: 10.18632/oncotarget.5020
|View full text |Cite
|
Sign up to set email alerts
|

Global phosphotyrosine survey in triple-negative breast cancer reveals activation of multiple tyrosine kinase signaling pathways

Abstract: Breast cancer is the most prevalent cancer in women worldwide. About 15–20% of all breast cancers are triple negative breast cancer (TNBC) and are often highly aggressive when compared to other subtypes of breast cancers. To better characterize the biology that underlies the TNBC phenotype, we profiled the phosphotyrosine proteome of a panel of twenty-six TNBC cell lines using quantitative high resolution Fourier transform mass spectrometry. A heterogeneous pattern of tyrosine kinase activation was observed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 64 publications
2
46
1
Order By: Relevance
“…3C–F). As previously reported36, we found that AXL mRNA levels were significantly increased in TNBC patients, compared to normal breast tissue (Fig. 2D, p = 0.033).…”
Section: Resultssupporting
confidence: 89%
“…3C–F). As previously reported36, we found that AXL mRNA levels were significantly increased in TNBC patients, compared to normal breast tissue (Fig. 2D, p = 0.033).…”
Section: Resultssupporting
confidence: 89%
“…As a novel third‐generation TKI, DCC‐2036 has a broader kinase inhibition profile than second‐generation TKIs, such as dasatinib, sorafenib and gefitinib. DCC‐2036 potently inhibits multitargets, including SRC, RAF, VEGFR2, AXL and MET, which are activated and/or highly expressed in multiple TNBC subtypes . Our study indicated that DCC‐2036 efficiently inhibits TNBC in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 63%
“…Recently, tyrosine kinases (TKs) have been suggested to be potential actionable targets due to their activation and high expression in multiple TNBC subtypes . The success of Herceptin (trastuzumab) in HER2‐positive breast cancer underlines the promise of targeting TKs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that different major signalling networks are activated specifically in TNBC 14,109,112 . Phosphorylation of HMGA1 turned on the IL4-mediated signalling pathway and enhanced the metastatic potential of TNBC tumors 109 .…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…However substantial changes in key components of this pathway (such as AKT and PI3K) were not observed in breast cancer subtypes 14 , consistent with the particularly aggressive nature of TNBC. Wu et al used a SILAC based quantitative phosphoproteomic approach to assess tyrosine kinase activity in TNBC and discovered multiple activated kinase signalling pathways 112 . Their phosphoproteomic analysis showed that AXL, a receptor tyrosine kinase, was highly phosphorylated in TNBC.…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%